2014
DOI: 10.5604/17322693.1102278
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interactions Between Anticancer Chemotherapeutics and Phenolic Compounds and Anticancer Synergy Between Polyphenols

Abstract: Chemoprevention has recently gained a new dimension due to the possibility of studying the mechanisms of action of chemopreventive agents at the molecular level. Many compounds have been proved to inhibit early stages of carcinogenesis in experimental models. These compounds include both recognized drugs (such as tamoxifen and nonsteroidal anti-inflammatory drugs) and natural constituents of edible and therapeutic plants, particularly polyphenols. Phenolics are characterized by high structural diversity and, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 0 publications
0
60
0
2
Order By: Relevance
“…[17] Some of the recent studies indicated that natural components of various plants such as cocoa, curcuma, green tea, soya and others have ability to prevent and cure cancer, through modulation of some signaling pathways, having some biological activities such as antiproliferative, proapoptotic and anti-angiogenic, so it can halt the carcinogenesis process. [18] Polyphenol compounds contained in cocoa extract have been identified to have chemopreventive effect, through several mechanisms including antiproliferation, induction of apoptosis, oxidation prevention, detoxification enzyme induction, host immune system regulation, antiinflammatory activity, and prevention of cellular signal that can produce carcinovenesis [19]. The application of cocoa extract before oxidative stress prevented DNA damage and increased the activity of antioxidant enzyme glutathion reductase and glutatihion peroxidase in cells induced with pro-oxidant, tetrabuthylhydroperoxide.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Some of the recent studies indicated that natural components of various plants such as cocoa, curcuma, green tea, soya and others have ability to prevent and cure cancer, through modulation of some signaling pathways, having some biological activities such as antiproliferative, proapoptotic and anti-angiogenic, so it can halt the carcinogenesis process. [18] Polyphenol compounds contained in cocoa extract have been identified to have chemopreventive effect, through several mechanisms including antiproliferation, induction of apoptosis, oxidation prevention, detoxification enzyme induction, host immune system regulation, antiinflammatory activity, and prevention of cellular signal that can produce carcinovenesis [19]. The application of cocoa extract before oxidative stress prevented DNA damage and increased the activity of antioxidant enzyme glutathion reductase and glutatihion peroxidase in cells induced with pro-oxidant, tetrabuthylhydroperoxide.…”
Section: Discussionmentioning
confidence: 99%
“…Still, each drug is administered to different types of cancer and at distinct doses among patients, they result in more or fewer side effects in the body. In this sense, it becomes essential to develop new drugs with lower or no toxicity, and with the ability to prevent pathological angiogenesis [19]. Researchers have thus focused in antiangiogenic molecules that occur naturally in plants.…”
Section: Antiangiogenic Drugsmentioning
confidence: 99%
“…Resistance is usually acquired when the tumor is able to growth, by enabling VEGF/VEGFR-2 independent pathways, thus promoting tumor angiogenesis [112]. An alternative to overcome the antiangiogenic drugs resistance is by their combination with other conventional therapies, including chemotherapy or radiation [19]. Combined therapies may have a synergistic effect when compared to the single drug therapies [115].…”
Section: Antiangiogenic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…This clearly indicates that the cytotoxic effect of Carica papaya leaf juice is not due to a single compound, but likely a number of constituents acting together to produce the overall effect. Many examples supporting this phenomenon can be found in reviews about additive or synergistic interactions in traditional and herbal phytomedicines (Williamson, 2001, Lewandowska et al, 2014, Ulrich-Merzenich et al, 2009, Rather et al, 2013. The assessment of synergism represents an emerging area in phytochemical research, seeking to explore improved therapeutic effects from herbal drugs used in traditional medicine (Zhang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%